2011
DOI: 10.1007/s10681-011-0515-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of markers linked to major gene loci involved in determination of fruit shape index of apples (Malus domestica)

Abstract: Fruit shape index (FSI) is one of the most important traits in apple. In this study, the inheritance of a FSI (ratio between height and diameter at the widest point of the fruit) was analysed in a hybrid population derived from 'Jonathan' 9 'Golden Delicious' (Malus domestica Borkh) using frequency distribution and molecular marker analysis. A binary distribution pattern was observed which matched a 31:1 segregation ratio for small: large FSI scores. This ratio can be explained by the segregation of five indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…In our study, two yearstable loci associated with FSI (Locus 1 and Locus 2) were mapped to 4.4-6.7 Mb and 7.4-7.5 Mb, respectively, on chromosome 11 of 'Jonathan'. Locus 2 was located near the previously reported QTL region (8.9-10.8 Mb on LG 11) using SSR linkage maps (Chang et al 2014), and that location was also close to a major gene in a study using bulked segregant analysis with the same population (Sun et al 2012). Although the present study did not detect significant QTLs of FSI trait in 2010 or 2011, a peak LOD was present at 5.8 cM of LG 11 of the 'Jonathan' linkage map (data not shown).…”
Section: Effect Of Population and Environment On Detection Of Stable mentioning
confidence: 52%
See 4 more Smart Citations
“…In our study, two yearstable loci associated with FSI (Locus 1 and Locus 2) were mapped to 4.4-6.7 Mb and 7.4-7.5 Mb, respectively, on chromosome 11 of 'Jonathan'. Locus 2 was located near the previously reported QTL region (8.9-10.8 Mb on LG 11) using SSR linkage maps (Chang et al 2014), and that location was also close to a major gene in a study using bulked segregant analysis with the same population (Sun et al 2012). Although the present study did not detect significant QTLs of FSI trait in 2010 or 2011, a peak LOD was present at 5.8 cM of LG 11 of the 'Jonathan' linkage map (data not shown).…”
Section: Effect Of Population and Environment On Detection Of Stable mentioning
confidence: 52%
“…Here, QTLs for fruit length were mapped at different LGs in 3 years, coinciding with weak correlations for the trait between 2008 or 2009 and 2014 (Table 1). However, FSI has high heritability in apple (Sun et al 2012) and a strong correlation among sampling years, as Diaz et al (2014) reported for melon. Huang et al (1997) suggested that stable QTLs of traits with high heritability are easy to detect under different environmental conditions.…”
Section: Effect Of Population and Environment On Detection Of Stable mentioning
confidence: 63%
See 3 more Smart Citations